2005
DOI: 10.1038/sj.eye.6702083
|View full text |Cite
|
Sign up to set email alerts
|

The management of primary rhegmatogenous retinal detachment not involving the fovea

Abstract: Aim To establish the likelihood of, and risk factors associated with, progression of 'macula-on' retinal detachment. Methods A multi-centre prospective observational study of patients with acute retinal detachment, not involving the fovea, was conducted over a 6-month period. Data collected included duration of symptoms, visual acuity, presence of posterior vitreous detachment, retinal drawings and subretinal fluid (SRF) distance from the fovea at a minimum of two time points. Results A total of 82 data sets f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 5 publications
0
44
0
4
Order By: Relevance
“…1,2 In a letter, Prasad 1 asserts that 'best evidence indicates that there is no benefit in urgent surgery as long as scheduled surgery can be performed within 7-10 days'. We are concerned that he has misread his supporting references, which are concerned with visual recovery in macula-off retinal detachments, including one entitled 'visual recovery in macula-off retinal detachments'.…”
Section: Sir Treatment Of Macula-on Retinal Detachmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 In a letter, Prasad 1 asserts that 'best evidence indicates that there is no benefit in urgent surgery as long as scheduled surgery can be performed within 7-10 days'. We are concerned that he has misread his supporting references, which are concerned with visual recovery in macula-off retinal detachments, including one entitled 'visual recovery in macula-off retinal detachments'.…”
Section: Sir Treatment Of Macula-on Retinal Detachmentsmentioning
confidence: 99%
“…2 The authors qualify their results with a number of study weaknesses that render meaningful conclusions virtually impossible, apart from the finding that if the macula is just about to come off it may well do so in the very near future. That the majority of patients with macula-on retinal detachments do not become macula-off before surgery does not mean that it is acceptable for some patients to lose vision because of undue delay.…”
Section: Sir Treatment Of Macula-on Retinal Detachmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies evaluated functional outcomes of RRD repair depending on the time point of surgery [6][7][8][9][10][11] . For example, Hassan et al [6] could find no effect on the final visual outcome for the first 10 days of duration of the detachment, but a decrease in visual acuity after 10 days and again after 6 weeks of symptom duration.…”
Section: Introductionmentioning
confidence: 99%
“…In the first 10 days after onset of symptoms, the timing of reattachment surgery does not seem to have an impact on visual outcome in macula-off situations. In cases of symptom duration >10 days, functional outcome may be affected adversely [6][7][8][9][10][11] . A recent study concluded that eyes treated up to 3 days after onset of loss of central vision have better final visual acuity than eyes with longer lag time [12] .…”
Section: Introductionmentioning
confidence: 99%